Criminal Dimensions of Forced Sterilization of Romani Women: A Focus on Gender-Based Violence and Deprivation of Liberty - Olga Koshevaliska; Roze Surlovska Ristevska (Journal of Liberty and International Affairs)
This paper examines the forced sterilization of Romani women as a serious violation of human rights and a fundamental denial of personal liberty. Drawing on legal, sociological, and feminist frameworks, the analysis demonstrates how this practice reflects intersecting forms of racial and gender-based discrimination within healthcare systems and state institutions. Romani women in vulnerable socio-economic circumstances have been systematically denied autonomy over their reproductive choices, highlighting broader patterns of structural exclusion. The findings emphasize the need to address forced sterilization not only as a criminal offense but also as a form of institutionalized violence that requires urgent legal, policy, and institutional reforms to protect personal liberty and advance reproductive justice.